Carbonic anhydrase inhibitor acetazolamide shifts synaptic vesicle recycling to a fast mode at the mouse neuromuscular junction - Bertone Cueto, Nicolás Iván (2017)
Acetazolamide (AZ), a molecule frequently used to treat different neurological syndromes, is an inhibitor of the carbonic anhydrase (CA), an enzyme that regulates pH inside and outside cells. We combined fluorescent FM styryl dyes and electrophysiological techniques at ex vivo levator auris longus neuromuscular junctions (NMJs) from mice to investigate the modulation of synaptic transmission and vesicle recycling by AZ. Transmitter release was minimally affected by AZ, as evidenced by evoked and spontaneous end-plate potential measurements. However, optical evaluation with FM-styryl dyes of vesicle exocytosis elicited by 50 Hz stimuli showed a strong reduction in fluorescence loss in AZ treated NMJ, an effect that was abolished by bathing the NMJ in Hepes. The remaining dye was quenched by bromophenol, a small molecule capable of diffusing inside vesicles. Furthermore, in transgenic mice expressing Synaptophysin-pHluorin (SypHy), the fluorescence responses of motor nerve terminals to a 50 Hz train of stimuli was decrease to a 50% of controls in the presence of AZ. Immunohistochemistry experiments to evaluate the state of the Myosin light chain kinase (MLCK), an enzyme involved in vesicle recycling, demonstrated that MLCK phosphorylation was much stronger in the presence than AZ than in its absence in 50 Hz stimulated NMJs. We postulate that AZ, via cytosol acidification and activation of MLCK, shifts synaptic vesicle recycling to a fast (kiss-and-run) mode, which changes synaptic performance. These changes may contribute to the therapeutic action reported in many neurological syndromes like ataxia, epilepsy, and migraine.